2020
DOI: 10.1039/d0ra00274g
|View full text |Cite
|
Sign up to set email alerts
|

Study on the biodegradability of modified starch/polylactic acid (PLA) composite materials

Abstract: In this work, polylactic acid/thermoplastic acetylated starch (PLA/TPAS) composites were prepared using PLA as a matrix material and TPAS as a modifier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…Acetic acid achieved a decrease (≤2 • C) in crystallization temperatures and a greater degree of disorder with lower enthalpies, while lactic acid at increased temperatures (2 to 4 • C) also caused a greater disorder of the structure. This behavior resembles that obtained by Yu et al [31]. The above allows us to conclude that TPS acts as a nucleating agent in PLA and that organic acids increase the crystallization speed.…”
Section: Thermal Analysis-tga Dscsupporting
confidence: 88%
“…Acetic acid achieved a decrease (≤2 • C) in crystallization temperatures and a greater degree of disorder with lower enthalpies, while lactic acid at increased temperatures (2 to 4 • C) also caused a greater disorder of the structure. This behavior resembles that obtained by Yu et al [31]. The above allows us to conclude that TPS acts as a nucleating agent in PLA and that organic acids increase the crystallization speed.…”
Section: Thermal Analysis-tga Dscsupporting
confidence: 88%
“…Polyethylene glycol (PEG) is an excellent plasticizer for PLA and can significantly enhance its elongation at break [60]. Moreover, PLA is very often mixed with starch in the presence of glycerin due to economic reasons and to improve the mechanical properties of PLA (e.g., increase toughness) by changing the concentration of starch in the composite [61]. Another study reported the improvement of tensile strength and elongation after blending PLA with starch particles.…”
Section: Miscibility With Other Polymersmentioning
confidence: 99%
“…The disparity found in standardization is also found in studies on the effects of various radiation types, with the majority of available research information focusing on UV-A and UV-B effects. While studying the biodegradability of PLA composites, Yu et al found that short-term UV exposure increases the tensile properties of the investigated materials, while long term exposure has an increasingly detrimental effect [34].…”
Section: Introductionmentioning
confidence: 99%